Вычислить √3^6 √5^4 √(-3)^4 √(-1,8)^2 Упростите выражение √x^12 √b^6 Найдите значение выражения √x^2-2x+1 при: x=5 x=0 x=10 Показать что: 4 меньше √17 меньше 5 3,1 меньше √10 меньше 3,2 7 меньше √59 меньше 8 Упростите вы...
Вычислить
√3^6
√5^4
√(-3)^4
√(-1,8)^2
Упростите выражение
√x^12
√b^6
Найдите значение выражения √x^2-2x+1 при:
x=5
x=0
x=10
Показать что:
4< √17 <5
3,1 < √10 <3,2
7< √59 <8
Упростите выражение
√(4-√5)^2
√(√3-2)^2
√(√8-3)^2
Ответ(ы) на вопрос:
√3^6= √(3^2*3^2*3^2)=27
√5^4= √(5^2*5^4)=25
√(-3)^4= √(-3^2)*(-3^2)=9
√(-1.8)^2=√3.24=1,8
Не нашли ответ?
Похожие вопросы